(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Premenstrual syndrome (PMS) is a set of physical and psychological symptoms such as mood disability, breast tenderness, food craving, fatigue, and depression. Fluoxetine and Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) usually are being administered for these patients. This study aimed to evaluate the effect of saffron plant in terms of its anti-inflammatory and anti-depressant effects compared to fluoxetine. Materials and Method: This study was a three-blind clinical trial that was carried out on working women and their relatives. Firstly, 164 patients with the premenstrual syndrome were selected, and they were randomly divided into two 82-person groups, including those who received fluoxetine and those who received saffron. Next, both groups were treated for two months. The data were collected in two stages through a self-designed questionnaire (on day 5 of menstrual cycle) and validated questionnaires of PRISM and Beck at the end of the period. Results: It was indicated that similar to fluoxetine, the use of saffron in PMS reduced the symptoms such as abdominal bloating, depression, and mood swing, but the latter could better relieve the breast and abdominal pain than fluoxetine. Conclusion: It was concluded that the use of medicinal herbs such as saffron could be effective in reducing the symptoms and they might cause fewer side effects than chemical drugs.